Respostas cardiorespiratórias frente ao método Treinamento Corretivo Postural (TCP)® - Lima, Marco Antonio de (2018)
The sedentary lifestyle is related to the low volume of physical activity leading to a series of chronic non-communicable diseases, such as cardiovascular, diabetes mellitus type 2, among others. The perspectives are those that improve the reversion of the picture, the physical training (TF) and the benefits for the improvement and maintenance of the health. In this way, TF can be planned and structured through volume, intensity and density, such as measurement and cardiorespiratory control variables, such as those that adjust to heart rate (HR), oxygen consumption (VO2), rate of the metabolic equivalent (MET) and the subjective perception of effort (PSE) of Borg, being used to calculate the energy expenditure (GE) of the activities. Among the current proposals for TF, Postural Corrective Training (TCP)® is presented as a method of aerobic gymnastics that presupposes antigLravity movements, performed in the frontal plane, as the basis of the functional work of posture. Based on the training of coordinating capacities, it aims not only to improve body posture, but also to promote the health and quality of life of its practitioners. However, there are still few studies regarding the behavior of cardiorespiratory variables during an initial session in the method. Thus, the objective of this study was to measure the HR, VO2 and GE in a 45 minute video-lesson method (ST) session in 19 young men (N = 19) aged 25,4 ± 5 years without previous contact with the method. Throughout the session, HR and VO2 were measured by Frequencimetro (Polar®) and ergospirometry, respectively. The collected analyzes were registered in an electronic database, submitted to tabulations in electronic spreadsheets, and later analyzed by the IBM® SPSS® software (Statistical Package for the Social Sciences), version 22.0. The Kolmogorov-Smirnov test was used to calculate the means and standard deviation and the ANOVA was used for multifactorial measurements, Tukey post-hoc p <0.05. Results: HR, VO2, MET during TCP® was the same for those evaluated in the course of time with PSE in the Borg scale of 9.5 ± 1.81, HR maintained a plateau equal to 126.7 ± 16.75. Relative HR (% FC) of the patients remained at 66 ± 7% of the HRmax, which was obtained in a growing treadmill test, performed prior to the (TCP)® video session. The consumption of VO2 was: 17.53 ± 2.45 ml.kg.min-1, a metabolic demand of 5 ± 1.62 MET and GE of: 296.7 ± 59.03 kcal with a respiratory quotient (QR) of 0.86 ± 0.04. The results demonstrate that a (TCP)® method can be characterized as a predominance of energy metabolism of the aerobic oxidative system, with moderate intensity and caloric expenditure, with an easy to moderate effort perception, for this population.